2010
DOI: 10.1524/ract.2010.1756
|View full text |Cite
|
Sign up to set email alerts
|

Complexation of Nd(III) with tetraborate ion and its effect on actinide(III) solubility in WIPP brine

Abstract: The potential importance of tetraborate complexation on lanthanide(III) and actinide(III) solubility is recognized in the literature but a systematic study of f-element complexation has not been performed. In neodymium solubility studies in WIPP brines, the carbonate complexation effect is not observed since tetraborate ions form a moderately strong complex with neodymium(III). The existence of these tetraborate complexes was established for low and high ionic strength solutions. Changes in neodymium(III) conc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
41
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(43 citation statements)
references
References 5 publications
1
41
1
Order By: Relevance
“…4 In an effort to understand the solubility limiting phases that may be present upon closure of the repository, Borkowski et al found that borate, not carbonate, is the primary complexant for trivalent actinide metals within the WIPP brines. 5 While not a trivalent cation under repository conditions, there is a large amount of uranium, approximately 6.5 × 10 5 kg, stored at WIPP that is projected to be found as a 50/50 mixture of uranium(IV) and uranium(VI). 4 As such, there exists the possibility that uranium(VI) and borate may come into contact and react within the repository as decaying nuclear wastes, leading to heating beyond ambient temperatures.…”
Section: Introductionmentioning
confidence: 99%
“…4 In an effort to understand the solubility limiting phases that may be present upon closure of the repository, Borkowski et al found that borate, not carbonate, is the primary complexant for trivalent actinide metals within the WIPP brines. 5 While not a trivalent cation under repository conditions, there is a large amount of uranium, approximately 6.5 × 10 5 kg, stored at WIPP that is projected to be found as a 50/50 mixture of uranium(IV) and uranium(VI). 4 As such, there exists the possibility that uranium(VI) and borate may come into contact and react within the repository as decaying nuclear wastes, leading to heating beyond ambient temperatures.…”
Section: Introductionmentioning
confidence: 99%
“…Recent complexation and speciation studies of neodymium(III), which acts as a surrogate of An(III) (An = actinide) in simulated WIPP brines have shown that borate competes with carbonate for An(III) complexation under the repository conditions. 10 The presence of the decaying nuclear waste will lead to heating beyond the ambient conditions in the deposit, and therefore the reactions of actinides with borates at moderate temperatures are important reactions to study in order to predict the fate of actinides in the repository.…”
Section: Introductionmentioning
confidence: 99%
“…These deposits contain borate in high concentrations in intergranular brines, and landmark work by Reed and coworkers has shown that borate, not carbonate, is the primarily complexant for trivalent cations in these repositories. [11] We recently showed that Pu III and Am III borates possess substantially different compositions, structures, and local coordination environments at the metal centers. [12] Our prediction was that the chemistry of Cm III III centers appear to be crystallographically related, but in fact differ by one coordinating water molecule.…”
mentioning
confidence: 99%